Understanding barriers and predictors of maternal immunization: Identifying gaps through an exploratory literature review. Issue 49 (26th November 2018) - Lutz, Chelsea S.; Carr, Wendy; Cohn, Amanda; Rodriguez, Leslie
Abstract: Background: The Advisory Committee for Immunization Practices recommends that all pregnant women receive the seasonal influenza vaccine and the tetanus toxoid, diphtheria toxoid, and acellular pertussis (Tdap) vaccine during every pregnancy. However, vaccination coverage rates are suboptimal among pregnant women in the United States, leaving these women and their unborn children at risk of vaccine-preventable diseases and their complications. Objectives: We sought to understand the current landscape of published literature regarding maternal immunization, including barriers to and predictors of vaccine acceptance, and identify gaps in the research in order to inform strategies for future programmatic improvement. Methods: We conducted a literature search using MEDLINE (OVID), PsychINFO, and CINAHL (Ebsco) databases. The search included published, English-language manuscripts that identified patient, provider, or system-level barriers to, predictors of, or interventions that improved uptake of maternal vaccines among pregnant women in the US. Studies were reviewed using an inductive thematic analysis approach. Results: We included 75 studies in our review. Pregnant women identified 25 different barriers to accepting recommended maternal immunizations; barriers related to vaccine safety perceptions were the most common. Healthcare providers identified 24 different barriers to vaccinating their pregnant patients. The most commonly cited barriers among healthcare providers were financial concerns. Eighteen different predictors of vaccine acceptance were identified. Receipt of a healthcare provider's recommendation was the factor most frequently reported as a reason for vaccination among pregnant women. Conclusions: We were able to identify gaps in the literature regarding maternal immunization and make recommendations for future research. Efforts to address the challenges of maternal immunization in the United States should include increasing the focus on Tdap, implementing more high-level assessments of safety perceptions and associated concerns, and determining most effective interventions.